2017
DOI: 10.1016/j.wasman.2016.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for critical raw material recovery from WEEE – The case study of gallium

Abstract: Gallium and gallium compounds are more frequently used in future oriented technologies such as photovoltaics, light diodes and semiconductor technology. In the long term the supply risk is estimated to be critical. Germany is one of the major primary gallium producer, recycler of gallium from new scrap and GaAs wafer producer. Therefore, new concepts for a resource saving handling of gallium and appropriate recycling strategies have to be designed. This study focus on options for a possible recycling of galliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Despite many lifecycle engineering methods developed, a systematic methodology to identify and take cross value-chain opportunities for closing the loop is missing [1]. The insight of how to tackle the CRM issue from the lifecycle perspective is also scarce; compare, e.g., the recovery of CRM at the end of life [5].…”
Section: State Of the Art In Theory And Practicementioning
confidence: 99%
“…Despite many lifecycle engineering methods developed, a systematic methodology to identify and take cross value-chain opportunities for closing the loop is missing [1]. The insight of how to tackle the CRM issue from the lifecycle perspective is also scarce; compare, e.g., the recovery of CRM at the end of life [5].…”
Section: State Of the Art In Theory And Practicementioning
confidence: 99%
“…The results showed 7% less precious metals after the pre-shredding phase, while the difference between preshredded PCBs and shredded PCBs indicated additional loss of 62% precious metals in the PCBs. Ueberschaar, Otto, and Rotter (2017) showed that relatively small shares of gallium bearing components on PCBs or in LEDs lead to a dilution with other materials in conventionally applied recycling processes. Ending in the pyrometallurgical process for copper and precious metals refining, gallium is transferred as oxidized form to the slag.…”
Section: Fate Of Critical and Precious Elements In Pre-treatment Procmentioning
confidence: 99%
“…Furthermore, the difference between preshredded PCBs (size < 8 mm) and shredded PCBs (size < 2.5 mm) indicates 62% less precious metals in the shredded PCBs compared with the preshredded PCBs. Ueberschaar et al (2017b) show that the relatively small shares of gallium bearing components on PCBs or in light emitting diodes (LEDs) lead to a dilution with other materials in recycling processes used conventionally. Ending in the pyrometallurgical process for copper and precious metals refining, gallium is transferred as oxidized form to the slag.…”
Section: The Fate Of Cms In Pre-treatment Processesmentioning
confidence: 99%